Myocardial strain analysis by 4D-speckle tracking echocardiography for prediction of coronary artery disease severity in patients with stable angina pectoris - Amol Bhore; Prasad Shah; Suhas Hardas; Madhusudan Asawa (Indian Heart Journal, 2023)
Objective: We sought to evaluate the myocardial strain by four-dimensional speckle-tracking echocardiography (4D-STE) in patients with stable angina pectoris (SAP) to determine the severity of coronary artery disease (CAD) based on the Gensini score. Methods: The present study comprised of 150 patients with SAP. Patients with history of SAP, normal left ventricular ejection fraction, and without regional wall motion abnormalities (RWMA) were scheduled for elective coronary angiography. Based on Gensini score, there were two groups: non-critical stenosis group [Gensini score (0–19), n = 117] and critical stenosis group [Gensini score ≥20, n = 33]. Correlation between Gensini score and 4D-STE strain parameters were investigated. Results: Out of 150 patients, critical stenosis group had significantly depressed values of all 4D-STE strain parameters than non-critical stenosis group (p < 0.001), except global radial strain (GRS) parameter. Significant positive correlation was found between Gensini score and 4D global longitudinal strain (GLS), global circumferential strain (GCS), global area strain (GAS) with Spearman's correlation coefficient (ρ) as 0.626, 0.548, and 0.631, respectively (p < 0.001), whereas significant negative correlation was found between Gensini score and GRS (ρ = −0.433, p < 0.001). A 4D GLS value of ≥ −17 had 84.9% sensitivity and 97.4% specificity, GAS ≥ −31 (90.9% sensitivity, 78.6% specificity), GCS ≥ −17 (69.7% sensitivity, 92.3% specificity), and GRS <47 (sensitivity 72.7%, specificity 76.1%) to detect critical CAD described by Gensini score ≥20. Conclusion: The 4D-STE can aid in the assessment of severe CAD stenosis with good sensitivity and specificity in the patients with SAP without RWMA on traditional echocardiography.